Alterations in mouse spinal cord and sciatic nerve microRNAs after the chronic constriction injury (CCI) model of neuropathic pain. (13th July 2020) - Wilkerson, Jenny L.; Jiang, Jinmai; Felix, Jasmine S.; Bray, Julie K.; da Silva, Lais; Gharaibeh, Raad Z.; McMahon, Lance R.; Schmittgen, Thomas D.
Highlights: In the mouse CCI model, 125 miRNAs are differentially expressed in the sciatic nerve. The differentially expressed miRNAs in sciatic nerve include miR-138 (decreased), miR-142-5p (increased) and the three members of the miR-183 cluster (decreased). Eleven miRNAs are differentially expressed in the spinal cord of mice with CCI. Abstract: Pain is one of the most common reasons to seek medical attention and chronic pain is a worldwide epidemic. There are currently no relevant biomarkers for the diagnosis of chronic pain, and new therapeutic strategies for chronic pain treatment are desperately needed. The chronic constriction injury (CCI) of the sciatic nerve is a widely used preclinical model of pathological neuropathic pain. Over the past decade, investigators have come to appreciate the many contributions of noncoding RNA including microRNA (miRNA), and other long and short noncoding (nc) RNAs. The development and/or maintenance of chronic pain could be controlled epigenetically through ncRNAs. Here we seek to characterize CNS tissues in a mouse model of neuropathic pain as this may serve to elucidate potential biomarkers relevant to pathological pain in humans. Male C57BL6/J mice (6 CCI and 6 sham procedure) underwent surgery for sciatic nerve ligation with chromic gut sutures. Following 7 days, mechanical allodynia was quantified using the von Frey assay. Mice were then euthanized for collection of spinal cord and sciatic nerve. cDNA was synthesized to 627 unique mature miRNAs from the total RNA. In the CCI mice that displayed mechanical allodynia, 11 and 125 miRNAs were differentially expressed (i.e., greater than 1.5-fold increase or decrease; P < 0.05) in the spinal cord and sciatic nerve, respectively, as compared to sham controls. Among those differentially expressed miRNAs in the sciatic nerve of CCI mice, the following passed the more stringent Bonfferoni correction: miR-138-3p, miR-138-5p and miR-676-3p, reduced and miR-142-5p, increased. Our data support miRNAs as promising therapeutic targets for the treatment of pathological pain.